1992
DOI: 10.1051/mmm:0199200302-3014100
|View full text |Cite
|
Sign up to set email alerts
|

Energy-filtering transmission electron microscopy in materials science

Abstract: Abstract. 2014 Energy-filtering transmission electron microscopy (EFTEM) with an imaging filter lens can combine the modes of electron spectroscopic imaging (ESI) and electron spectroscopic diffraction (ESD), and different modes can be used to record an electron energy-loss spectrum (EELS). Therefore, an EFTEM can make full use of the elastic and inelastic electron-specimen interactions. This review summarizes the possibilities of EFTEM for applications in materials science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…EFTEM imaging is performed at Gaussian focus, as the image contrast results from the intrinsic differences in chemistry or electronic structure between the phases. 10 In recent years, chemical imaging of organic materials via EFTEM imaging has become increasingly popular. For example, the microstructure of multiphase systems has been probed via core-loss elemental mapping, [11][12][13][14][15] and the spatial distribution of carbon bonding states in a triphase polymer composite has also been mapped.…”
Section: Introductionmentioning
confidence: 99%
“…EFTEM imaging is performed at Gaussian focus, as the image contrast results from the intrinsic differences in chemistry or electronic structure between the phases. 10 In recent years, chemical imaging of organic materials via EFTEM imaging has become increasingly popular. For example, the microstructure of multiphase systems has been probed via core-loss elemental mapping, [11][12][13][14][15] and the spatial distribution of carbon bonding states in a triphase polymer composite has also been mapped.…”
Section: Introductionmentioning
confidence: 99%
“…Energy filtering transmission electron microscopes allow one to record images that are formed exclusively by electrons that have undergone a specific energy loss. Selecting only those electrons that have caused an element‐specific inner‐shell excitation and after removing a background, one may quickly obtain so‐called elemental maps, which contain the two‐dimensional distribution of a single element in the specimen ( Craven et al ., 1978 ; Reimer et al ., 1992 ; Hofer et al ., 1995 ; Reimer, 1995). While this description might suggest a straightforward interpretation, Kohl & Rose (1985) showed that one has to consider the quantum mechanical nature of the scattering process as well as the influence of the microscope to understand the intensity distribution in highly resolved (< 10 nm) elemental maps ( Golla & Kohl, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Energy-filtering transmission electron microscopy (EFTEM) is now a well-established tool for imaging elemental distributions complementing standard analytical techniques such as energy-dispersive X-ray spectrometry (EDXS) or electron energy-loss spectrometry (EELS) (Leapman and Hunt, 1992;Krahl, 1990;Mayer et al, 1994;Hofer et al, 1995a;Reimer et al, 1992). In particular, EFTEM explores the rich information provided by the EEL-spectrum in a spatial resolved manner.…”
Section: Introductionmentioning
confidence: 99%